2011
DOI: 10.4236/jwarp.2011.33022
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Textural Properties of Bovine Bones Char under Different Conditions

Abstract: Environmental pollution is today a very important issue and the development of low cost materials and different sources need to be investigated. Our research group for several years she has been the development of adsorbent materials for industrial wastewater treatment and rivers. In this research compares the porosity developed by two different treatments using bovine bones to adsorb metal ions. Using bovine bones as raw material, two carbonized samples were obtained under different conditions. One of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…These observations indicate that graphitic components and/or quinone moieties in BC may contribute to the observed electron mediation activity of the BC. However, unlike plants biomass in which lignin and cellulose are the main substrates for biochar formation, , bones consist of organic collagens together with 65–70% inorganic substances, mainly apatite . With an ordered inorganic composite as a hard template, collagens undergo pyrolysis to form porous carbon with a high defect density, both structurally and due to heteroatom dopings, resulting in high electron conductivity. ,,, Although a systematic study of the unique role of bone chars as electron conductors and redox mediators is lacking, we cannot rule out the contribution of specific functional groups and structures to the electron mediation activity of BC.…”
Section: Resultsmentioning
confidence: 99%
“…These observations indicate that graphitic components and/or quinone moieties in BC may contribute to the observed electron mediation activity of the BC. However, unlike plants biomass in which lignin and cellulose are the main substrates for biochar formation, , bones consist of organic collagens together with 65–70% inorganic substances, mainly apatite . With an ordered inorganic composite as a hard template, collagens undergo pyrolysis to form porous carbon with a high defect density, both structurally and due to heteroatom dopings, resulting in high electron conductivity. ,,, Although a systematic study of the unique role of bone chars as electron conductors and redox mediators is lacking, we cannot rule out the contribution of specific functional groups and structures to the electron mediation activity of BC.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the proximate analysis of goat bones showed that the ash content was 50% higher than that of other bone constituents, namely, 49.43%. Moreno-Piraján et al [39] reported that bone consists of 60% inorganic components (hydroxyapatite), 10% water, and 30% organic components (bone matrix proteins). Kacang goat bone extraction using alcalase and neutrase increased the gelatin yield compared to those without enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…8,10) 이 중 흡착 성능이 가장 좋은 불소 흡착제는 동 물의 뼈를 태워 만든 골탄이다. 8) 뼈의 65~70%는 무기물인 Hydroxyapatite (HAP, Ca 10 (PO 4 ) 6 (OH) 2 )로 구성되었으며, 8,11) HAP를 구성하고 있는 OH -가 F -와 치환되어 불소를 제거 할 수 있다. 12,13) 특히, 골탄은 주변에서 쉽게 구할 수 있고 폐 기물을 이용한다는 이점을 갖는다.…”
Section: 서 론unclassified